Moralitas Keadilan: Imperatif Moral Orang Katolik - Paulus Tolo (STIPAS St. Sirilus Ruteng, 2021)
The most problematic term in social relationships is justice. It coversall dimensions in human life. Since the way people understand themeaning of justice differs from time to time and from generations toother generations, it is worthy to trace the original meaning of justice.This article tries to describe the root of justice in the religious realm.Justice is regarded as a virtue which is imprinted in the human being.Human beings are created in the image of God. As a consequence, beinghuman means being just as God, the creator is just. Practicing justicein human relations is a way of making justice which stems from Godcan be tangible. This is the imperative of doing justice in the world.